Distributions of Rhizostoma pulmo (Macri, 1778) between the Kızılırmak and the Yeşilırmak coast of the Black Sea, Türkiye - Dönmez Memet Ali; Bat Levent (Oceanological and Hydrobiological Studies)
This study examined the seasonal distributions of the medusa Rhizostoma pulmo along the coasts of the southern Black Sea between Kızılırmak and Yeşilırmak between April 2008 and March 2010. Monthly abundance and biomass values were determined, as well as population parameters. The effect of temperature on medusa distribution was also investigated. Results showed that medusa abundance and biomass were highest in autumn, following a period of increased temperature. In contrast, medusa was not observed during the spring season. It was possible to observe the R. pulmo individuals for five months for the first term of investigation period (2008-2009), and seven months for the second term (2009-2010). The highest abundance value was found to be 10 n/m2 (November 2008 and September 2009) and the highest biomass value was 12.587,5 g/100 m3 (October 2009).